Intrinsic and extrinsic flaws of the nomogram predicting bone-only metastasis in women with early breast cancer: An external validation study. (December 2016) - Ouldamer, Lobna; Bendifallah, Sofiane; Chas, Marie; Boivin, Laura; Bedouet, Lea; Body, Gilles; Ballester, Marcos; Daraï, Emile
Abstract: Background: The recently developed MDACC nomogram purports to predict the risk of bone-only metastasis in women with early breast carcinoma based on five clinical and pathological characteristics. We set out to externally validate and assess its robustness using a tertiary breast cancer centre database. Methods: All consecutive women treated for early breast cancer in our centre between January 1989 and December 2013 and who had all the nomogram variables documented were eligible for analysis. Results: We identified 1255 eligible women for external validation analysis. The median follow-up was 54 months (range: 1–312) and time to initial metastasis 20 months (range: 1–80). The correspondence between the actual bone-only metastasis and the nomogram predictions implied poor calibration of the nomogram in the validation cohort, be it in the whole cohort or when stratified by breast cancer subtype. Conclusion: This external validation study of the MDACC nomogram showed limitations in its generalizability to a new and independent European patient population. Highlights: Nomogram to identify individuals at higher risk of bone-only metastasis in women with breast cancer. Low calibration using the nomogram both for the whole population and when stratified by breast cancer subtype. Late-onset bone metastasis is significantly higher in oestrogen receptor-positive women. The study showed limitations in the nomogram generalizability to a new and independent patient population.